2022
DOI: 10.3389/fpubh.2022.946186
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes among twin pregnancies with gestational diabetes mellitus: A nine-year retrospective cohort study

Abstract: ObjectiveTo compare the outcomes between gestational diabetes mellitus (GDM) vs. non-GDM twin gestations.MethodsA retrospective cohort study of 2,151 twin pregnancies was performed in a tertiary hospital in Foshan, China, 2012–2020. Pregnancy and neonatal outcomes were compared between women with vs. without GDM using 1:1 propensity score matching (PSM) and multivariable logistic models. For neonatal outcomes, generalized estimating equation (GEE) approach was used to address the intertwin correlation.ResultsO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 56 publications
(52 reference statements)
1
13
0
Order By: Relevance
“…Additionally, levels of diabetogenic hormones of human placental lactogen, which is secreted by the placenta into maternal circulation and serves as a physiologic antagonist to insulin, and estrogen have been reported to be higher in pregnancies with female neonates than with male neonates 30,31 . A previous study found gravidae with GDM were more likely to be associated with dichorionic twins, which have two separate placentas, compared with gravidae with monochorionic twin gestations 32 . In our study, our same‐sex fetal pairs (ie M‐M and F‐F) had relatively equal proportions of MCMA, MCDA and DCDA pairings with no differences in rates of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, levels of diabetogenic hormones of human placental lactogen, which is secreted by the placenta into maternal circulation and serves as a physiologic antagonist to insulin, and estrogen have been reported to be higher in pregnancies with female neonates than with male neonates 30,31 . A previous study found gravidae with GDM were more likely to be associated with dichorionic twins, which have two separate placentas, compared with gravidae with monochorionic twin gestations 32 . In our study, our same‐sex fetal pairs (ie M‐M and F‐F) had relatively equal proportions of MCMA, MCDA and DCDA pairings with no differences in rates of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Included into this retrospective cohort study were all the women who carried twin pregnancies and gave birth at a large tertiary perinatal center in southwestern China between January 1, 2016 and December 31, 2022. The exclusion criteria included: (1) single pregnancy; (2) lack of first-trimester ultrasound examination for chorionicity or gestational age determination; (3) pre-existing diabetes; (4) missing GDM screening results; (5) birth before gestational 28 weeks; (6) complications related to monochorionic placentation, such as twin-to-twin transfusion syndrome and selective fetal growth restriction; (7) monochorionic monoamniotic twins; (8) reduction in fetuses; and (9) fetal chromosomal or structural anomalies. To avoid confounding effects from pregnancy, only the first delivery during the study period was analyzed.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…GDM increases not only maternal complications, such as pre-eclampsia, premature rupture of membranes (PROM), placental abruption, and postpartum hemorrhage, but also adverse perinatal outcomes, including macrosomia, intrauterine growth retardation (IUGR), neonatal hypoglycemia, and neonatal respiratory distress syndrome [2,3]. Mounting evidence suggests that high body mass index (BMI), advanced maternal age, and assisted reproductive technology (ART) are risk factors for the occurrence of GDM [1,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of GDM in twin pregnancies is significantly higher than that in singleton pregnancies [ 8 ], at 21.9% [ 9 ] in multiple pregnancies versus 14.8% [ 10 ] in singleton pregnancies in China. Advanced maternal age, obesity, ART, and Asian ethnicity, regarded as risk factors for GDM in twin pregnancies [ 11 13 ], have been widely considered.…”
Section: Introductionmentioning
confidence: 99%